Modelo de simulação NS-2 para o protocolo DNP3 sobre o protocolo de rede sem fio IEEE 802.15.4 para simulação de baixo custo de aplicação smart grid - Pereira, Cássia Correia da Silva [UNESP] (2015)
Over the last decades, the challenges in the electricity sector have significantly increased, either by the issues regarding the way energy is generated and distributed by the consumer's attitude towards the electrical grid. In order to restructure the business model in the electricity sector, countries around the world have decided to invest in a concept known as Smart Grid. This system includes technologies such as digital, information and communication Technology (ICT). This concept aims to optimize and automate the electricity sector. The major changes proposed by the implementation of the Smart Grid are: higher network reliability, less failures in the power supply, lower time and costs of maintenance in the network, more accurate records of energy use by the consumer; and insertion of new energy sources in the network, contributing to reducing carbon dioxide emissions. Thus, investments in communication technologies is considered a key component for the performance of Smart Grids, as this technology demands diversified communication protocols that have to be fast and might involve a complex communication network. Among the existing communication protocols, the Distributed Network Protocol 3.0 (DNP3) is a protocol based on the specifications of the IEC (International Electrotechnical Commission) and adapted for use on highly secure applications with moderate data transmission rates. Several studies have pointed to possible use of the DNP3 protocol in conjunction with other communication standards such as IEEE 802.3, IEEE 802.11 and IEEE 802.15.4. The IEEE 802.15.4 is a standard for low power consumption and it has been disseminated as an appropriate solution for wireless sensor networks in several areas, such as industrial, commercial, residential and academic. The implementation of a heterogeneous communication network - to study and evaluate the behavior of a particular technology - is a highly costly process. However, computer ...